Nutraceutical Value of Sesame Oil - Gauthaman, K.; Saleem, T.S. Mohamed (Pharmacognosy Reviews)
Nutrients, herbals and dietary supplements are major constituents of nutraceuticals which make them active in maintaining health, act against various disease conditions and thus promote the quality of life. Drug as dietary supplements play a major role to alleviate all type of disease. The sheer number and type of dietary supplements available is overwhelming, and it’s hard to know which offer health benefits and which are merely giving false promises - often the information about supplements is confusing or unclear. From ancient time globally the peoples were using the sesame oil as dietary source. Sesame oil is known dietary source having putative antioxidant property. In this review we summarized the medicinal value of sesame oil with respect to phytochemistry and pharmacological activity. This article must provide the data for the researcher to develop the molecule from sesame oil to treat many type life threatening diseases.
Keywords: Sesame oil; Antioxidants; Dietary supplements; Sesamum indicum; Oxidative stress